Internal Migration and Depression Among Junior High School Students in China: A Comparison Between Migrant and Left-Behind Children - Zheng, Xiaodong; Zhang, Yue; Jiang, Wenyu (Frontiers in Psychology, 2022)
Using data from the China Education Panel Survey (CEPS), which was a nationally representative sample of junior high school students, this study examined the association of internal migration with depression among migrant and left-behind children, while exploring the moderating effect of gender difference and the mediating effects of social relationships. The results showed that migrant children had a significantly lower level of depression than left-behind children. Further, the difference in mental health between migrant children and left-behind children was more prominent for boys than girls. The mechanism analyses indicated that compared to left-behind children, internal migration positively predicted parent-child relationships and peer relationships of migrant children, which in turn reduced their depressive symptoms. Although migrant children suffered from a higher level of teacher discrimination than their left-behind counterparts, it had no significant relationship with depression after controlling for children’s social relationships with parents and peers. Our findings suggested that migrating with parents was helpful to reduce children’s depressive symptoms in comparison with being left behind. Therefore, actions should be implemented to reduce the occurrence of involuntary parent-child separation and the prevalence of children’s depressive disorders due to institutional constraints. In addition, necessary treatments are needed to improve the psychological well-being of disadvantaged children, especially among left-behind children with mental illness.